Pengaruh Pelatihan dan Komunikasi Terhadap Kinerja Karyawan PT Indonesia Power Unit Bisnis Pembangkitan (UBP) Mahakam (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the importance of improving employee performance in supporting the operational success of PT PLN Indonesia Power Generation Business Unit (UBP) Mahakam. Training and internal communication are two main factors that are believed to increase employee work effectiveness, but their implementation has not shown optimal results. The aim of this research is to analyze the influence of training and communication on employee performance at UBP Mahakam. The research method used was quantitative with a survey approach by distributing questionnaires to 144 employees. Data were analyzed using multiple linear regression to test the relationship between variables. The research results show that training and communication simultaneously have a significant effect on employee performance. Partially, training has a positive and significant influence, as does communication which has been proven to increase motivation and work clarity. These findings imply the importance of developing relevant training programs and open communication to support increased workforce productivity. Companies are advised to systematically evaluate training needs and strengthen internal communication channels as a strategic effort to achieve organizational goals.